Bacteriological study of urinary tract infection to children in Kirkuk city - Dr.Muhsin Hamad Edham (Kirkuk Journal of Science, 2017)
this study has been conducted to examine the existence of the bacteria causing urinary tract infections (UTI) for children and its isolation .Besides ,this study aims at testing the sensitivity of this bacteria to antibiotics in order to recognize the active antibiotic against its in order to study the impact of such factors as age and sex of the child on its spread, 100 samples of urine from children (aged 1 day to 15 years ) suffering from (UTI )from julio. 1, 2015—octubre,1-2015. when this culture was planted in suitable cultural media,45 sample showed a positive bacterial growth at %45.Other 55 samples did not show any bacterial growth at %55. Later,the growing bacterial colonies were isolated and diagnosed by microscopical,cultural and biochemical tests. The study comes up with the conclusion that the Escherichia coli was the most prevalent pathogenic causes..It represented 20 cases of infection at %44,4.The percentage of female infection was %34,4 and the male percentages was %10. the proteus spp recorded 12 cases of infeaction at %26,6 the pseudomonas recorded 4 cases,the enterobacter spp recorded 3 cases ,the streptococcus faecalis,citrobacter spp,staph citreus recorded 2 case only.The percentage of female infection was greater than male infection in all isolates besides most infections at1-5 years old children were reduced,The Escherichia coli showed hyper sensitivity to ciprofloxacin and amikacin at %90 while it was resistant to tobrmycin and erythromycin. the proteus showed higher sensitivity to ciprofloxacin ,amikacin andTobramycin at%100 but it was resistant to Erythromycin .The klebsiella showed higher sensitivity to nalidixic acid,ciprofloxacin and Nitrofurantion but it was resistant to erythromycin . The isolates of pseudomonas showed its hyper sensitivity to Tobromycin,Gentamicin ,tetracycline and Amikacin but it was medium sensitive to Ciprofloxacin,Erythromycin. The Entrobacter spp showed its hyper sensitive to Nitrofurantion, Ciprofloxacin but it was resistant to erythromycin ,while the Citrobacter spp showed its intermediate sensitivity to all used antibiotics. The streptococcus faecalis showed that it is hyper sensitive to Nalidixic acid at%100 but it was resistant to Nitrofurantion and Pencillin, the staphylococcus citreus showed that it is sensitive to Nalidixic acid at%90 and medium resistant to Azithromycin , pencillin.